2020
DOI: 10.15330/pcss.21.3.503-509
|View full text |Cite
|
Sign up to set email alerts
|

Solid gas and electrochemical hydrogenation properties of the R1-xR’xMgNi4-yCoy (R, R’ = Y, La, Ce) alloys

Abstract: New R1-xR’xMgNi4-yCoy (R, R’ = Y, La, Ce; x = 0.5; y = 0, 1, 2) alloys have been synthesized by powder sintering method, and their crystal structure and hydrogen storage properties have been studied. X-ray diffraction analysis showed that R1-xR’xMgNi4-yCo alloys belong to the MgCu4Sn-type structure. The synthesized alloys absorb hydrogen at room temperature and hydrogen pressure 0.1-10 bar. For some of the studied compounds, the formation of hydrides with cubic and orthorhombic structures was found. Highest hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Ітрій та церій є елементами групи РЗМ і утворюють споріднені сполуки до таких в системі La-Mg-Ni. Ми у [18] дослідили ефект такого заміщення для сплавів LaMgNi 4 . Праць, які присвячені вивченню сплавів на основі YMgNi 4 та CeMgNi 4 , не так вже й багато [19][20][21][22].…”
Section: вступunclassified
“…Ітрій та церій є елементами групи РЗМ і утворюють споріднені сполуки до таких в системі La-Mg-Ni. Ми у [18] дослідили ефект такого заміщення для сплавів LaMgNi 4 . Праць, які присвячені вивченню сплавів на основі YMgNi 4 та CeMgNi 4 , не так вже й багато [19][20][21][22].…”
Section: вступunclassified
“…Also, lowering the Mg content decreases the equilibrium pressure. , The studies of the electrochemical properties of such R 1– y Mg y Ni 4– x Co x compounds did not demonstrate such an outstanding improvement of the hydrogen capacity versus the Co content. Only a small amount of Co ( x = 0.5 for La 1– y R y MgNi 4– x Co x (R = Pr or Nd, y = 0 or 0.5); , x = 1 for La 1– y R y MgNi 4– x Co x (R = Y or Ce, y = 0 or 0.5); x = 0.33 for LaMgNi 4– x Co x ) slightly increases the discharge capacity while further increasing the Co content leads to the deterioration of the electrochemical properties. Additionally, Pr or Nd for La substitution improves the cyclic stability of the corresponding electrodes. , On the other hand, electrode materials with a larger Mg content ( y = 1.2) are characterized by improved electrochemical capacity due to both weight lowering and enhanced solid–gas H capacity …”
Section: Introductionmentioning
confidence: 99%
“…The increase in hydrogen capacity and kinetics during solid–gas hydrogenation by Co substitution was first reported for YMgNi 4– x Co x ( x = 0, 2, and 4) compounds. 3 Similar results were obtained for RMgNi 4– x Co x (R = Nd 4 or Tb, 5 with x = 0–3 for Nd, and up to 4 for Tb), La 1– y R y MgNi 4– x Co x (R = Pr 6 or Nd, 7 y = 0 or 0.5, x = 0–3), La 1– y R y MgNi 4– x Co x (R = Y or Ce, y = 0 or 0.5, x = 0–2), 8 and (R, R′) 2– y Mg y Ni 4– x Co x (R, R′ = Pr, Nd; y = 0.8–1.2; x = 0–2) 9 compounds. As for the Mg content in (R, R′) 2– y Mg y Ni 4– x Co x compounds, it should be larger than y = 0.8 to avoid amorphization.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of [10][11][12][13][14][15][16][17][18][19][20] studied a series of AB3 and A2B7 alloys, where a mixture of REM was used and the substitution of Ni for Co and Mn was applied, and confirmed the positive effect of alloying on the electrochemical characteristics of electrode materials. The detailed studies of REM-Mg-Ni,Co systems demonstrated also the positive influence of Co-substitution on the hydrogenation properties of the AB2 alloys [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%